NIR-to-vis photon upconversion in rubrenes with increasing structural complexity. Issue 12 (16th March 2021) - Radiunas, Edvinas; Dapkevičius, Manvydas; Naimovičius, Lukas; Baronas, Paulius; Raišys, Steponas; Juršėnas, Saulius; Jozeliūnaitė, Augustina; Javorskis, Tomas; Šinkevičiūtė, Ugnė; Orentas, Edvinas; Kazlauskas, Karolis
Abstract : Peripheral linking of rubrene emitters is found to deliver enhanced TTA efficiency vs. core linking. This provides valuable insight for their rational modification towards improved NIR-to-vis photon upconversion efficiency in the solid state. Abstract : Rubrene is the most widely used triplet–triplet annihilation (TTA) emitter for NIR-to-vis photon upconversion (UC), however, strong singlet fission (SF) in the solid films quenches its emission and hampers practical TTA-UC applications. Herein, the issue was addressed by decorating the rubrene with sterically demanding 3, 5-di- tert -butylphenyl side-moieties at the periphery and the core to result in 40-fold enhancement of the emission quantum yield. Nevertheless, the sterically crowded rubrenes were found to exhibit lower sensitized UC performance compared to the conventional rubrene, which was ascribed to inefficient triplet energy transfer from a sensitizer and poor TTA (for the core-modified rubrene only). By exploiting the distinct feature of rubrenes to simultaneously express both SF and TTA in the solid films, their TTA efficiency was assessed independently from TET in the sensitizer-free films. The results implied a trade-off between suppressed SF and enhanced TTA in the rubrene emitters, which could be addressed via careful selection of the degree of sterical hindrance and linking position of the side-moieties. Thorough analysis of the prompt and delayed fluorescence revealed that the bulky side-moieties at the periphery do not impede TTA, i.e., it is as efficient as that of unsubstituted rubrene, whereas these moieties linked directly to the core suppress TTA dramatically. The current study unveils an advantage of the peripheral linking vs. core linking pattern of rubrene emitters, thereby providing valuable insights for their rational modification towards improved NIR-to-vis UC efficiency in the solid state.